2015
DOI: 10.1130/g36082.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of controls on silicate weathering in tropical mountainous rivers: Insights from the Isthmus of Panama

Abstract: The Isthmus of Panama comprises a lithologically diverse andesitic oceanic arc of Late Cretaceous to Holocene age; it has large spatial variation in rainfall, displays a large range of physical erosion rates, and, therefore, is an ideal location to examine silicate weathering in the tropics. We use a multiyear data set of river chemistry for a 450 km transect across the Cordillera Central of west-central Panama to investigate controls on chemical weathering in tropical small mountainous rivers. Sea-salt correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…Our long-term cation yields (corrected for sea salt contribution in precipitation and non-silicate contribution of Ca and Mg) for the PCW range from 2.85 to 19.3 t/km 2 /year, whereas our suspended sediment yields range from 124 to 1,494 t/ km 2 /year (Table 1; Supplementary Tables 1 and 2). Our cation yields are in the lower range of those previously determined for watersheds across the Panamanian isthmus 10 , whereas our suspended sediment yields are within the range of those calculated using an earlier dataset for the PCW 31 . When we analyzed each river individually over the length of the study period using a Pearson correlation, all but one watershed showed a statistically significant (p < 0.05) positive relationship (r avg ≥ 0.75) between cation yields and mean annual precipitation at Lake Gatun ( Fig.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Our long-term cation yields (corrected for sea salt contribution in precipitation and non-silicate contribution of Ca and Mg) for the PCW range from 2.85 to 19.3 t/km 2 /year, whereas our suspended sediment yields range from 124 to 1,494 t/ km 2 /year (Table 1; Supplementary Tables 1 and 2). Our cation yields are in the lower range of those previously determined for watersheds across the Panamanian isthmus 10 , whereas our suspended sediment yields are within the range of those calculated using an earlier dataset for the PCW 31 . When we analyzed each river individually over the length of the study period using a Pearson correlation, all but one watershed showed a statistically significant (p < 0.05) positive relationship (r avg ≥ 0.75) between cation yields and mean annual precipitation at Lake Gatun ( Fig.…”
supporting
confidence: 71%
“…In a search for controls, studies have recognized the strong positive feedback between physical and chemical weathering [1][2][3] and noted the importance of underlying volcanic lithologies on maintaining elevated chemical yields [4][5][6][7][8][9][10][11] . Others have identified strong correlations/associations between weathering yields and precipitation/ runoff 2,3,9,10,12 and, more recently, land use/landcover practices 10,11,13 . Yet, despite their important contribution to silicate weathering, few datasets for SMRs exist at high temporal resolution 10,14 and/or duration 15 for such high-yield terrains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest 505 and most significant relationship in our dataset is between cosmogenically-derived erosion rates 506 and chemical weathering of silicate rocks in the same watersheds (Goldsmith et al, 2015, R 2 = 507 0.41, p = 0.014, n = 14). Similarly, a positive relationship between chemical and physical erosion 508 measured using 10 Be has been reported by Riebe et al (2003Riebe et al ( , 2004 and Riebe and Granger (2012) and von Blanckenburg (2005).…”
mentioning
confidence: 94%
“…Using the data of Goldsmith et al (2015), we too find a positive relationship between 504 chemical weathering (their data) and total erosion rates (our 10 Be data) in Panama. The strongest 505 and most significant relationship in our dataset is between cosmogenically-derived erosion rates 506 and chemical weathering of silicate rocks in the same watersheds (Goldsmith et al, 2015, R 2 = 507 0.41, p = 0.014, n = 14).…”
mentioning
confidence: 99%